Synthesis of guest molecules for studies of urea inclusion compounds. - Adams, Angela Dee (Kansas State University, 2011)
Most urea inclusion compounds (UICs) are known to share a common packing arrangement in which the urea host forms helical ribbons held together by hydrogen bonds to form a series of linear, hexagonal tunnels. Because UICs can encapsulate a wide variety of linear guest molecules, they serve as useful model systems for probing mechanisms of crystal growth and molecular recognition. In this thesis, the syntheses (or attempts thereof) of six compounds that will serve as consequential guest molecules in studies of UICs are presented. These compounds are (5S,6S)-2,9-decanedione-d2, 1,6-dicyanohexane-1,1,6,6-d4, 1,11-undecanedioic acid, bis(3-oxobutyl) adipate, 2,16-heptadecanedione, and 2-eicosanone. With the exception of (5S,6S)-2,9-decanedione-d2, whose synthesis remains incomplete, detailed synthesis and crystal growth of the UICs of these compounds are discussed. Ongoing studies with the UICs containing these guests include the determination of the absolute configuration of UICs, the study of guest conformer population changes via solid-state NMR, the development and identification of novel ferroelastic UICs, and the classification of guest ordering in a series of alkanedione UICs.
Keywords: Urea inclusion compounds; Crystallography; Ferroelasticity; Absolute configuration; Chemistry (0485)